PEMBERDAYAAN IBU PKK KELURAHAN GALUNG MELALUI INOVASI PRODUK ICE CREAM SECANG SEBAGAI PELUANG USAHA - Irfan, Muhammad; Agustina, Agustina; Fahrodi, Deka Uli; Said, Nur Saidah (LPPM Universitas Nusa Mandiri, 2026)
This community service program was carried out in Galung Village, Banggae District, Majene Regency, involving women’s community groups (PKK) as partners. The program aimed to enhance participants’ knowledge and skills in processing milk into secang ice cream by utilizing sappan wood (Caesalpinia sappan L.) extract as a natural colorant and antioxidant source, making it a promising functional ingredient. The implementation method consisted of participatory counseling, demonstration- based training, hands-on practice, and mentoring with monitoring and evaluation. The results of the activity showed a significant increase in all aspects of participants’ knowledge, namely dairy processing technology from 48% to 91%, the use of secang wood from 31% to 86%, ingredients from 0% to 90%, production stages from 0% to 83%, business benefits from 0% to 92%, marketing strategies from 0% to 90%, and interest in making secang wood ice cream from 78% to 100%. These outcomes demonstrate the effectiveness of the program in improving technical skills, entrepreneurial motivation, and local product innovation capacity. Secang ice cream has the potential to be developed into a sustainable home-based business that empowers women economically. Further development through product diversification, packaging innovation, and local government support is expected to expand its impact and replication in other regions.